Between evocation and political integrity: César Moro's civic concerns between Lima and Puebla - Cavagnaro Farfán, Franco (2025)
The article rescues the aesthetic appreciations and preferences of the poet César Moro on various monuments in Lima and Mexico, based on the buried debate between him and the architect Paul Linder in Las Moradas, in the answers to two questionnaires, in Los anteojos de azufre (1957) and in his correspondence. From this comparison, the reasons for his rejection of modern architecture, his condemnation of crimes against culture, arboricides and noise are exposed. With these premises, his faith in the evocation of the forms of the past in the face of the new and the consideration of the architecture of Mexico (Puebla) as an example of the present time that the “traditional pre-Hispanic and colonial forces” have, in addition to their belief in political integrity within a community